Urban Indians in Phoenix schools, 1940-2000 - Amerman, Stephen Kent (University of Nebraska Press, 2010)
"In the latter half of the twentieth century, tens of thousands of Native American families moved to cities across the United States, some via the government relocation program and some on their own. In the cities, they encountered new forms of work, entertainment, housing, and education. In this study, Stephen Kent Amerman focuses on the educational experiences of Native students in urban schools in Phoenix, Arizona, a city with one of the largest urban Indian communities in the nation. The educational experiences of Native students in Phoenix varied over time and even in different parts of the city, but interactions with other ethnic groups and the experience of being a minority for the first time presented distinctive challenges and opportunities for Native students., Using oral histories as well as written records, Amerman examines how the Phoenix schools tried to educate and assimilate the Native students alongside Hispanic, Asian, black, and white students and how Native children, their parents, and the Indian community at large responded to this new urban education and the question of their cultural identity. Reconciling these pressures was a struggle, but many found resourceful responses, charting paths that enabled them to acquire an urban education while still remaining Indian."–Pub. desc.
SCSU Faculty Scholar Award
Keywords: 20th century; 20th century; Education; 20th century; Indians of North America; 20th century; Public schools; 20th century; Urban schools; 20th century; Urbanization; Arizona; Cultural assimilation; Education; History; Indians of North America; Phoenix; Social aspects; award_winner; dept.his; faculty_collection